Step-by-step explanation:
Move expression to the left side and change its sign
5
y
−
3
+
10
y
2
−
y
−
6
−
y
y
+
2
=
0
Write
−
y
as a sum or difference
5
y
−
3
+
10
y
2
+
2
y
−
3
y
−
6
−
y
y
+
2
=
0
Factor out
y
and
−
3
from the expression
5
y
−
3
+
10
y
(
y
+
2
)
−
3
(
y
+
2
)
−
y
y
+
2
=
0
Factor out
y
+
2
from the expression
5
y
−
3
+
10
(
y
+
2
)
(
y
−
3
)
−
y
y
+
2
=
0
Write all numerators above the least common denominator
5
(
y
+
2
)
+
10
−
y
(
y
−
3
)
(
y
+
2
)
(
y
−
3
)
=
0
Distribute
5
and
−
y
through the parenthesis
5
y
+
10
+
10
−
y
2
+
3
y
(
y
+
2
)
(
y
−
3
)
=
0
Collect the like terms
8
y
+
20
−
y
2
(
y
+
2
)
(
y
−
3
)
=
0
Use the commutative property to reorder the terms
−
y
2
+
8
y
+
20
(
y
+
2
)
(
y
−
3
)
=
0
Write
8
y
as a sum or difference
−
y
2
+
10
y
−
2
y
+
20
(
y
+
2
)
(
y
−
3
)
=
0
Factor out
−
y
and
−
2
from the expression
−
y
(
y
−
10
)
−
2
(
y
−
10
)
(
y
+
2
)
(
y
−
3
)
=
0
Factor out
−
(
y
−
10
)
from the expression
−
(
y
−
10
)
(
y
+
2
)
(
y
+
2
)
(
y
−
3
)
=
0
Reduce the fraction with
y
+
2
−
y
−
10
y
−
3
=
0
Determine the sign of the fraction
−
y
−
10
y
−
3
=
0
Simplify
10
−
y
y
−
3
=
0
When the quotient of expressions equals
0
, the numerator has to be
0
10
−
y
=
0
Move the constant,
10
, to the right side and change its sign
−
y
=
−
10
Change the signs on both sides of the equation
y
=
10
Check if the solution is in the defined range
y
=
10
,
y
≠
3
,
y
≠
−
2
∴
y
=
10
Answer:
2
Step-by-step explanation:
|x| means absolute value
|x| means if x is positive or negative, its still positive
-5|x|+4=14
-5|x|=10
|x|= -2
answer is 2
Answer:
3 = x
Step-by-step explanation:
0 > 3x - 3 - 6
You want to group up the -3 and -6 first
0 > 3x - 9
Then you want to add 9 to each side to cancel out the negative 9 on one side.
0 > 3x - 9
+9 +9
9 > 3x
Now you just divide by 3 on each side
![\frac{9 = 3x}{3}](https://tex.z-dn.net/?f=%5Cfrac%7B9%20%3D%203x%7D%7B3%7D)
3 = x
The first answer
Step by step
His first year costs $8,000
So our total amount to start with is $8,000
His second year will cost 12% more than his first so $8,000 • 1.12 = $8,960
Our total is now $16,960
His third year will again will be 12% more than his last year so $8,960 • 1.12 = 10,035.2
Our total is now $26,995.2
His last year will be 12% more than his previous year so $10,035.2 • 1.12 = $11,239.42
Our final total is $38,234.62
Which rounded equals $38,235